The gospel according to wild indigo - Cassells, Cyrus (Crab Orchard award series in poetry., 2018)
"The Gospel according to Wild Indigo, Cyrus Cassells's sixth volume of poetry, is comprised of two exhilarating song cycles and is his most intensely lyrical and ecstatic poetry to date"--